2013
DOI: 10.1080/17421772.2013.833343
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Fiscal Decentralization on Household Income Inequality: Some Empirical Evidence

Abstract: In this paper we investigate the effects of fiscal decentralization on income inequality using a sample of 23 OECD countries over the period 1971-2000. We utilize novel and robust measures of fiscal decentralization based on different degrees of expenditure and tax autonomy of sub-central governments. We also use several different specifications to tackle the potential endogeneity and reverse causality issues. Our results highlight the importance both of the nature of fiscal decentralization -expenditure versu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 71 publications
1
30
0
4
Order By: Relevance
“…Earth observation allowed us to calculate the Night Light Development Index (NLDI) which we used to measure regional inequality. This index is calculated based on the methodology for the calculation of the Gini coefficient, commonly used to measure regional inequality [43,48,53,67].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Earth observation allowed us to calculate the Night Light Development Index (NLDI) which we used to measure regional inequality. This index is calculated based on the methodology for the calculation of the Gini coefficient, commonly used to measure regional inequality [43,48,53,67].…”
Section: Methodsmentioning
confidence: 99%
“…At the same time, to our knowledge, this is the first attempt to introduce EO solutions in measuring SDG 10 at the sub-national level.We chose Romania as the study area for three reasons: it is one of the most unequal countries of the European Union (EU) [34-40]; these regional inequalities have been generated in the last 20 years [41][42][43]; and the country has started an economic development process from a low level, making it very suitable for the application of night-time light data from satellite imagery [44]. However, the results are not limited to the area of study, as will be shown in the following parts of the article.The literature on regional inequalities focused until recently on local tax income from household surveys and GDP per capita from national accounts, as a complex measure of economic development highlighting inter-regional differentials worldwide [34,[45][46][47][48][49][50][51][52][53] or applying case studies in a Romanian context [34][35][36]42].However, the above-mentioned economic indicators used to measure regional inequalities have several limitations, such that GDP is measured directly only at the national level, while at the regional level it is calculated indirectly with a two-year delay compared to the national one [3,54]. Compared to traditional statistical data, night-time lights satellite images have a number of advantages: regional inequality can be calculated locally in real time (instead of waiting two years for the indirect calculations from national accounts); they have higher temporal resolution; and they can be obtained free of charge.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Related to that, a number of authors have recently started to investigate the different implications of revenue versus expenditure decentralization in relation to GDP growth (e.g., Jin and Zou 2005;Gemmell et al 2013), fiscal discipline (e.g., Afonso and Hauptmeier 2009;Escolano et al 2012), or income distribution (Boadway et al 2003;Sacchi and Salotti 2013). As expected, this has resulted in different empirical findings depending on the series used to measure fiscal decentralization, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Beside, it also showed a positive and significant influence between the fiscal capacities to financial independence. Sacchi and Salotti (2014a), investigating the effects of fiscal decentralization on household income inequality, for a sample of 23 OECD countries over the period of 1971-2000, find that a higher degree of tax decentralization is associated with a more unequal distribution of income within a country. More recently, Sepúlveda and Martinez-Vazquez (2011) proved that higher levels of fiscal decentralization appears to reduce poverty as long as the share of sub-national expenditure is not greater than one-third of total government expenditure.…”
Section: Literature Reviewmentioning
confidence: 99%